PEMINDAHAN MAKAM SEBAB PERBEDAAN PANDANGAN POLITIK - Idrus L Idrus L (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2019)
AbstractBasically, dismantling the unlawful grave as long as the bones of the corpse allegedly still in it. But there are some views of the scholars who allow the dismantling of graves if they meet the Shariah law'. It is forbidden to move a corpse without any element of benefit, both for the corpse itself and for the living, otherwise it is permissible to move the corpse if there is an element of benefit, both for the corpse and for the living. Demolition and removal of graves cannot be justified because of differences in political views between landowners or endowments and grave experts because it is not an emergency reason that requires demolition and removal of graves. The context of an emergency that allows the dismantling and removal of graves is condemning human benefit that can not be avoided.Keywords: Graveyard Transfer, Political Views.AbstrakPada dasarnya, membongkar kuburan haram hukumnya selama tulang mayatnya diduga masih ada di dalamnya. Namun ada beberapa pandangan para ulama yang membolehkan dilakukannya pembongkaran kuburan jika memenuhi hukum Syara’. Haram hukumnya memindahkan mayat tanpa ada unsur kemaslahatan, baik untuk mayat itu sendiri maupun orang hidup sebaliknya dibolehkan memindahkan mayat bila terdapat unsur maslahat, baik bagi mayat maupun bagi orang hidup. Pembongkaran dan pemindahan makam tidak bisa dibenarkan hanya karena alasan perbedaan pandangan politik antara pemilik tanah atau pewakaf dan ahli kubur karena bukan alasan darurat yang mengharuskan pembongkaran dan pemindahan makam. Konteks darurat yang membolehkan pembongkaran dan pemindahan makam adalah mengecam kemaslahatan manusia yang tidak bisa dihindari.Kata Kunci: Pemindahan Makam, Pandangan Politik.